PENERAPAN RES IPSA LOQUITOR DALAM MALPRAKTIK DI RUMAH SAKIT - Yana Sylvana; Gunawan Widjaja (Cross-border, 2022)
Medical service is a relationship between health care providers and patients. The health care professional or physician must operate ethically and circumspectly in order to avoid malpractice. Medical malpractice is defined as any professional error made by a physician, including an act that a physician should not perform. An action indicating suspected malpractice does not necessarily result in a court judgment, and some instances remain unresolved. The Res Ipsa Loquitur doctrine or the thing speaks for itself, which is consistent with existing regulations in favor of the victim, does not require the victim to show the doctor's negligence process. This doctrine provides justice for patients who are victims by proving that the malpractice case is real or indirect evidence. The evidence is conducted in accordance with civil law, and proof of the element of negligence suffices to establish the facts.